CD86 ‐Positive Mature Tertiary Lymphoid Structures Are Associated With CD8 + T‐Cell Infiltration and Favorable Clinical Outcomes in Pancreatic Ductal Adenocarcinoma - Takaomi Seki; Kenichiro Araki; Takehiko Yokobori; Hayato Ikota; Norio Kubo; Takamichi Igarashi; Mariko Tsukagoshi; Norihiro Ishii; Yasuo Hosouchi; Hiroshi Saeki; Ken Shirabe (Annals of Gastroenterological Surgery, 2026)
ABSTRACT Aims Although tertiary lymphoid structures (TLSs) contribute to antitumor immunity, the significance of CD86 expression within mature TLSs in pancreatic ductal adenocarcinoma (PDAC) remains unclear. This study evaluated CD86‐positive mature TLSs as a marker of an immunologically active tumor microenvironment. Methods We analyzed 128 treatment‐naive patients with PDAC who underwent curative resection. TLSs were evaluated by hematoxylin and eosin staining and immunohistochemistry for CD4, CD8, CD20, CD21, CD23, and CD86. TLS maturation, CD86 expression, TLS density and diameter, intratumoral T‐cell infiltration, and clinical outcomes were assessed. Multiplex immunofluorescence for CD8 and Granzyme B was performed in selected cases. Results TLSs were identified in 124 patients. Among TLS‐positive cases, 13, 21, and 90 were classified as immature, intermediate, and mature TLSs, respectively. Mature TLSs were associated with increased intratumoral CD8 + T‐cell infiltration compared with TLS‐absent cases ( p = 0.027), whereas CD4 + T‐cell infiltration did not differ significantly. CD86‐positive mature TLSs were associated with higher intratumoral CD8 + T‐cell infiltration ( p = 0.002), greater TLS density, and larger TLS diameter than CD86‐negative mature TLSs. Multiplex immunofluorescence confirmed that most CD86‐positive cells co‐expressed CD20. Exploratory CD8/Granzyme B analysis suggested a higher proportion of Granzyme B‐expressing CD8 + T cells in CD86‐positive mature TLSs. Patients with CD86‐positive mature TLSs showed favorable clinical outcomes. Conclusion CD86‐positive mature TLSs may represent a pathological feature associated with an immunologically active tumor microenvironment in PDAC, as reflected by increased intratumoral CD8 + T‐cell infiltration, a higher proportion of Granzyme B‐expressing CD8 + T cells in the exploratory analysis, and favorable clinical outcomes.